2007
DOI: 10.1093/jee/100.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Spinosad Interacts Synergistically with the Insect Pathogen Metarhizium anisopliae Against the Exotic Wireworms Agriotes lineatus and Agriotes obscurus (Coleoptera: Elateridae)

Abstract: We determined that spinosad interacts synergistically with the biocontrol agent Metarhizium anisopliae (Metch) Sorokin to increase the mortality of two wild-collected wireworm species, Agriotes lineatus (L.), and Agriotes obscurus (L.). Bioassays were performed using a M. anisopliae isolate originally acquired from a local wireworm cadaver. M. anisopliae was applied as a soil drench at 3.3 x 10(2) and 10(4) conidia per gram sand, respectively. Soil drenches also were prepared using a commercial formulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 0 publications
1
46
0
3
Order By: Relevance
“…Chemicals can make insects more susceptible to EPF even when used at relatively low doses (Quintela and McCoy 1998;Ericsson, Kabaluk, Goettel, and Myers 2007;Shah et al 2007a). Chemical insecticides may influence insect behaviour such as reduced preening which prevents removal of spores and increased movement, which increases acquisition of inoculum (Shah et al 2007a;Butt et al unpublished observations).…”
Section: Cropmentioning
confidence: 99%
“…Chemicals can make insects more susceptible to EPF even when used at relatively low doses (Quintela and McCoy 1998;Ericsson, Kabaluk, Goettel, and Myers 2007;Shah et al 2007a). Chemical insecticides may influence insect behaviour such as reduced preening which prevents removal of spores and increased movement, which increases acquisition of inoculum (Shah et al 2007a;Butt et al unpublished observations).…”
Section: Cropmentioning
confidence: 99%
“…Studies on insect hosts other than mosquitoes have indicated that fungal infection can act synergistically with insecticides, increasing the impact of otherwise sublethal insecticide doses (24)(25)(26). Mixtures of M. anisopliae and deltamethrin were shown to enhance virulence of both components when tested against ticks, indicating synergistic effects that would enhance the effectiveness of low fungi and insecticide concentrations (27).…”
mentioning
confidence: 99%
“…Asian long-horned beetles treated with imidacloprid produced significantly fewer Metarhizium conidia compared to beetles not treated with imidacloprid (Russell et al, 2010). Similar synergism was observed in wireworms (Ericsson et al, 2007). Cockroaches (Blatella germanica) were killed significantly faster when fed on imidacloprid or propetamphos after a topical application of M anisopliae whereas chlorpyrifos and cyfluthrin were additive (Neves et al, 2002).…”
Section: Interactions Of Fungal Disease and Pesticides In Other Insectsmentioning
confidence: 89%